Stability of pork jerky with betalain powder from bougainvillea (Bougainvillea spectabilis) in vacuum and non-vacuum packaging. - Coscolluela, Patricia Ysabel Villanueva
Philippines is considered as a disaster prone area, hence there is a need to develop stable food to be available for distribution during survival situation. A disaster food must be accessible to provide necessary nutrition and must have a long storage life. Meat jerky is an example of an appropriate survival food. The study aimed to determine the shelf-life of pork jerky with the addition of betalain powder from Bougainvillea (Bougainvillea spectabilis). Also, the study evaluated the suitability of two various packaging conditions, vacuum and non-vacuum packaging for extending the stability of the product. The changes in the physicochemical (moisture content, water activity, and pH), microbiological (yeast and mold count and total plate count), and sensorial properties (descriptive and general acceptability) of the betalain-treated pork jelly in vacuum and non-vacuum packaging at ambient condition (27-30°C) were only monitored for 10 days despite of the targeted storage time of 50 days due to numerous growth of microorganisms. The values obtained from the betalain-treated pork jerky were compared to a control. The physicochemical and microbiological properties of the betalain-treated pork jerky and the control formulation stored in vacuum and non-vacuum packaging at ambient condition had increased over time. Using Independent two-sample T-test (α = 0.05), there was no significant difference between the physicochemical and microbiological properties of the product and control formulation in both packaging conditions. Although, not significantly different, however, the parameters measured in the betalain-treated pork jerky stored in vacuum packs were lower. It was also observed that the rate of increase was slower in vacuum packaging than in non-vacuum packaging. The betalain-treated pork jerky was evaluated by the panelist to have a moderate herbal flavor and aroma. It was rated to be moderately chewy and dark pink in color. The results showed that the betalain-treated pork jerky has a limited storage life of only 5 days, thus cannot be distributed as disaster food. It is recommended to further to further study the processing of pork jerky with the addition of betalain powder from Bougainvillea (Bougainvillea spectabilis).